The Impact of the Defense Attorney on Plea Decision-Making: An Experimental Analysis - Suiter, Emily (Criminal justice and behavior, 2024)
Most criminal court cases are resolved through a plea, yet the plea decision-making process remains largely unexplored in comparison to other phases of case processing. With defendants reliant on their defense attorney during the plea process, it stands to reason that the characteristics of the defense attorney would impact plea decision-making. To assess this possibility, we administered an experimental vignette to a national sample, manipulating defense attorney type, race, sex, experience, familiarity with other courtroom workgroup members, and empathy toward the defendant. We found that respondents were more likely to accept a plea offer if the defense attorney was experienced and empathic. When the defense attorney was private, experienced, familiar, or empathic, respondents rated their defense attorney as more qualified, which then influenced their acceptance of the plea offer. Uncertainty of the outcome, consequences of a plea, and reasonableness of the plea offer were the common motivators in decision-making.